Development of smart access and tracking on information resources (smart library) system using radio frequency identification (RFID) technology - Harun, Hasma Khairul Nisak (2008)
In recent years, Radio Frequency Identification (RFID) technology has become widespread automatic identification and data capture technology with huge potential in broad range of industry sectors including libraries. The main goal of this thesis is to give more visibility concerning the use of the RFID technology applied to the library environment in SIRIM Berhad. For almost a decade, SIRIM Berhad library has never failed in disseminating technical information and wealth of knowledge to its customers through the Library Management System. Limitations imposed by the system include complexity in system integration and enhancement, slower circulation rate and inefficiency in inventory identification and tracking due to the barcode system. Therefore, this thesis presents the development of an integrated Smart Library System which utilises the RFID technology with the aim of replacing current system and speeding the patron identification, material circulation and inventory tracking process, besides providing broad accessibility and efficient traceability of information. In adherence to the software engineering discipline, the Smart Library System is developed according to the Software Development Process defined in the organisation Quality Management System (ISO 9001:2000). This thesis focuses on the Object-Oriented method aided with Unified Modelling Language (UML). Substantial findings on salient characteristics of RFID are presented to incorporate the technology in the system development. The results of this thesis not only demonstrate a successful integration of RFID technology in library environment to promote improvement in service within the libraries, it also delivers required documentations according to DOD-STD-2167A standard. In conclusion, the thesis achieves its objectives to consistently apply software engineering practice in delivering the system that complies with the organisation's needs besides producing documentations that meet the selected standard.